2022
DOI: 10.1186/s40360-022-00633-y
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib activates autophagy by inhibiting the mTOR signaling pathway and prevents apoptosis in nucleus pulposus cells

Abstract: Background Intervertebral disc degeneration results from a variety of etiologies, including inflammation and aging. Degenerated intervertebral discs feature down-regulated extracellular matrix synthesis, resulting in losing their ability to retain water and absorb compression. Celecoxib is a well-known selective cyclooxygenase-2 inhibitor for treating arthritis and relieving pain. Nevertheless, the mechanism of Celecoxib for treating inflammation-related intervertebral disc degeneration has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Pro inflammatory cyclines such as IL‐1β, IL‐17, and TNF‐α are associated with inter regional disc generation, and their expression is significantly increased in degenerative inter regional disc issue (Chen, Yasen, et al, 2022; Tan et al, 2022; Zhang, He, et al, 2019). Nuclear factor kappa B (NF‐κB) is a multifunctional transcription factor that plays an important role in the regulation of inflammatory response, cell promotion, and apoptosis (Zhu et al, 2019).…”
Section: Cell Autophagy and Iddmentioning
confidence: 99%
“…Pro inflammatory cyclines such as IL‐1β, IL‐17, and TNF‐α are associated with inter regional disc generation, and their expression is significantly increased in degenerative inter regional disc issue (Chen, Yasen, et al, 2022; Tan et al, 2022; Zhang, He, et al, 2019). Nuclear factor kappa B (NF‐κB) is a multifunctional transcription factor that plays an important role in the regulation of inflammatory response, cell promotion, and apoptosis (Zhu et al, 2019).…”
Section: Cell Autophagy and Iddmentioning
confidence: 99%
“…Another recent study focused on the use of cxb in rat NP cells, which showed promising results in restoring extracellular matrix formation and minimizing oxidative stress by activating the mammalian target of rapamycin and downstream proteins to accelerate autophagy machinery. However, this effect has not been investigated in AF cells [11,18,19].…”
Section: Celecoxib's Effect On Il-1β-treated Hafcsmentioning
confidence: 99%
“…Of the two direct functions of STING, it is clear that the inflammatory activity of STING needs to be suppressed in the treatment of IVDD, while the upregulation of autophagy can improve IVDD. Exercise, certain endogenous hormones, or drugs can activate autophagy to protect NP cells from aging and apoptosis, and inhibit ECM degradation ( 154 , 155 ). As described in the first section of this article, autophagy mediates STING signal attenuation.…”
Section: Sting and Age-related Diseases In The Musculoskeletal Systemmentioning
confidence: 99%